Does ownership concentration affect financial performance? evidence of Malaysian healthcare sector / Noor Sharida Badri Shah ... [et al.] - Badri Shah, Noor Sharida; Mohd Zaidi, Nur Qaisara Auni; Mohd Zulkifli, Shaliza Azreen; Shekh Zain, Rozihanim; Muhammad Yusuf, Noor Hafizha; Shafai, Nor Anis (Universiti Teknologi MARA, Perlis, 2025)
Corporate Ownership Concentration stand as critical pillars shaping the success of modern businesses. Today, this matter is fostered by a new set of parameters in a global economy and facing the huge challenges in corporate governance issues. This empirical study investigates the effect of ownership concentration on financial performance (Return on Asset) in Malaysian Healthcare sector. The study conducted empirical research using a sample of fourteen (14) companies operating within the Malaysian healthcare sector. STATA 14 was employed to run panel data analysis; panel specification test, diagnostic test, descriptive statistics, correlation analysis and regression analysis. The study found that ownership concentration significantly influences the financial performance of healthcare firms, as it provides greater control and influence over strategic decisions, promotes accountability and long-term orientation, and facilitates active monitoring of management. The understanding of this relationship is crucial for optimizing ownership structures, mitigating agency costs, and enhancing overall sector performance, ultimately leading to improved healthcare provision in Malaysia.